Nanomedicine for treatment of diabetes in an aging population: state-of-the-art and future developments - Krol, Silke; Ellis-Behnke, Rutledge; Marchetti, Piero (Nanomedicine. Nanotechnology, biology and medicine, 2012)
Nowadays diabetes, especially type 2 diabetes (which is strongly related to the Western diet and life-style), has developed worldwide into an epidemic disease. Nanomedicine aims to provide novel tools for diagnosis, therapy and point-of-care management of patients. Several nanotechnological approaches were developed to improve life quality for patients with insulin-dependent diabetes. They facilitate blood glucose management by non-invasive glucose measurement as well as insulin administration mainly by delivering the fragile protein as protected and targeted formulation via nasal or oral route. In the present review the oral or nasal insulin delivery by polymeric nanoparticles is discussed with focus on physiological change either related to the disease, diabetes or age-related metabolic variations influencing insulin release and bioavailability. One critical point is that new generations of targeted nanoparticle based drugs are developed and optimized for certain metabolic conditions. These conditions may change with age or disease. The influence of age-related factors such as immaturity in very young age, metabolic and physiologic changes in old age or insufficient animal models are still under-investigated not only in nanomedicine but also generally in pharmacology. Summarizing it can be noted that the bioavailability of insulin administered via routes others than subcutaneously is comparably low (max. 60%). Moreover factors like changed gut permeability as described for diabetes type 1 or other metabolic peculiarities such as insulin resistance in case of type 2 diabetes also play a role in affecting the development of novel nanoparticulated drug preparations and can be responsible for unsuccessful translation of promising animal results into human therapy. In future insulin nanoparticle development for diabetes must consider not only requirements imposed by the drug but also metabolic changes inflicted by disease or by age. Moreover new approaches are required for prevention of the disease.